Case report: Video-assisted minimally invasive mitral and pulmonary valve replacement as reoperation in patient with situs inversus totalis - Salamate, Saad; El-Sayed Ahmad, Ali; Bayram, Ali; Sirat, Sami; Bakhtiary, Farhad (Frontiers in Cardiovascular Medicine, 2023)
Dextrocardia with situs inversus totalis is a rare congenital condition. We report herein a first experience of video-assisted minimally invasive mitral and pulmonary valve replacement through right anterior mini-thoracotomy as reoperation in patient with this complex anomaly. The good clinical and cosmetic results demonstrate that this innovative technique can be safely performed even in difficult anatomical conditions.